Hidrodinâmica das descargas fluviais para o estuário do Rio Jaguaribe (CE.) - Dias, Francisco José da Silva (2007)
The increasing of greenhouse gases and of the human population, results in growing awareness of water resources managers of freshwater availability in the world, mostly in the tropics. Knowing that Brazil still presents an excellent availability of freshwater, with 33.000 m3.inhabitant.years, the Ministry of the Environment, in a recent publication, stands out that the Basins of the Eastern Northeast Atlantic, in which the Jaguaribe river is inserted, already presents a high level of estress of their water bodies, with only 45% of the minimum value of the 2.500 m3.inhabitant.years suggested by the Organization of United Nations (ONU) as being the minimum required to the exercise of the human social and economic activities. The water discharge of the Jaguaribe river basin, with 72,043 km2 of area and 633 km2 of extension, measured at the nearest seaward station, indicates historical average outflows varying between 14 ± 23 m3.s-1 in the dry season and up to 235 ± 434 m3.s-1 in the rain season. However, this fluvial discharge can not be considered as discharging to the ocean, because the basins reservoirs holds back 87% of the fluvial flow. The modeling of river flow performed in the present study at tidal river zone (ZR) and the mixture zone (ZM) interface under quadrature tides in February and June 2006, and under spring tide, in September 2005, showed total outflow varying between 58 and 183 m3.s-1 in the evaluated period. The residence time (TR) of estuarine waters was dependent on the inter-annual climatic variability varying from 3 to 2 hours in the dry station, in 2005 and 2006, respectively, and 12 hours at the season, evidencing that the volume of freshwater is not a limiting main factor for the ability of the water mass to breach the operating sea strength in the region, but the total outflow is significant, mainly during the dry station when the estuary is leached by sea waters that increase its renew capacity. Highest salinities was observed in the periods when the estuary presented lower input of fluvial waters, reaching the 36,1. The particulate suspended matter (MPS) varied seasonality between 7 and 89,7 mg/L. The MPS in September of 2005 and June of 2006 was strongly organic, and the MPS observed in February of 2006 was mostly of carbonate origin. The discharges of MPS and metals associated with it to the estuary, presented the highest values in the period of larger fluvial flow, varying between 1,9 104 x ton.year-1 in September of 2005 (12% of freshwater origin) to 2,5 105 x ton.year-1 in the period with 95% of freshwater. The same behavior is observed for the discharges of metals, such as; Fe, which in September of 2005 presented a discharge of 3 x 102 ton.year-1, whereas in the period of larger fluvial flux of 1,2 x 104 ton.year-1, having as an exception the Pb flux, which presented the highest values in the period of marine domain.